Gerakan Perempuan Subaltern Ekofeminisme dalam Melawan Pembangunan PLTU 2 Indramayu - Cusdiawan Cusdiawan; Oekan S. Abdoellah; Firman Manan (Journal of Education, Humaniora and Social Sciences (JEHSS), 2022)
This research examines the struggle of women in rejecting development that is considered damaging to the environment. The problem asked in this study, namely "How is the process of the subaltern ecofeminism women's movement in Indramayu against the construction of PLTU  2 ?". Meanwhile, the purpose of the research is to describe the process of the subaltern ecofeminism women's movement in Indramayu against the construction of PLTU 2. This research was conducted using a qualitative method with a feminist perspective, and took place in Mekarsari Village, Patrol District, Indramayu Regency which became the site of PLTU 2 construction. subaltern groups, because of their position outside of social and political representation, this development will further marginalize them. Therefore, they took the fight in the form of social movements. In this movement, women affirm the spirit of ecofeminism. This article looks at the process of the movement with a social movement integration approach (political opportunity structure, mobilization structure and framing process), so that the factors of political economy structure, mobilization structure and framing are considered an important part of the process of emergence and development of a movement